Review on the Injury and Repair Mechanism of Skeletal Muscle Contusions - LIN Jianping; WANG Hao; GUO Mingling; WANG Shizhong; CHEN Shaoqing (康复学报)
We reviewed the injury and repair mechanism of skeletal muscle contusions (SMC), it is explained in five aspects, such as the theories of myosatellite cell proliferation and differentiation, Ca2+ mediated membrane repair, endoplasmic reticulum stress (ERS) and autophagy. Muscle regeneration plays an important role in the repair of SMC, it relies on the differentiation of surrounding satellite cells to restore muscle function. The signal pathways involve in the regulation of myoblast differentiation of myosatellite cells mainly including RBP-J κ/Notch signal, Wnt signal and P13K/Akt/mTOR signal pathway. Notch signal pathway regulates the self-renewal and differentiation of myosatellite cells to maintain the homeostasis of muscle stem cells. And P13K/Akt/mTOR signal pathway has a positive regulation effect on myoblast differentiation of myosatellite cells and can promote skeletal muscle regeneration. However, current research on the role of Wnt signal pathway in the regeneration of mature muscle is controversial, and more studies are needed in the future. Ca2+ mediated membrane repair is essential for the survival of muscle cells after SMC. Ca2+ is blocked due to structural damage or functional decline of calcium pump after SMC, leading to calcium depletion in the endoplasmic reticulum (ER). Ca2+ dysregulation contributes to abnormal protein production by promoting mitochondrial reactive oxygen species (ROS) production and disrupting protein folding in the ER, thus, the abnormal folding protein in the ER is increased. Once the retention and aggregation of which exceeds its threshold value, ERS occurs. Excessive ERS can mediate autophagy through PKC or FAM134B pathways. Autophagy maintains homeostasis through the self-degradation of abnormal organelles or misfolded proteins. As for the mechanism of autophagy in the repair of SMC, in addition to the induction of excessive ERS, it has been reported that SMC induces insufficient oxygen supply to local tissues, promotes the production of a large number of ROS or activation of AMPK signal pathway, and then induces mitochondrial autophagy, which maintains the stability of mitochondria and saves energy consumption, so as to achieve the purpose of promoting repair after SMC. Although the injury and repair mechanism of SMC is complex, there are some crossovers between the above theories. Therefore, the research on the injury and repair mechanism of SMC can be further explored around the above theories, to clarify how the above different theories play a synergistic role in different stages of injury and repair after SMC.